Solitary fibrous tumor of the pancreas. - Chetty, R; Jain, R; Serra, S (2009)
A 67-year-old woman was found to have an incidental pancreatic mass on computed tomographic examination of her abdomen in the course of investigation of hematuria. The radiologic features were of a hypervascular mass in the uncinate process of the head of the pancreas, and a preoperative diagnosis of a neuroendocrine tumor was favored. A Whipple procedure was performed. The uncinate process contained a 2.6-cm well-circumscribed mass. Histologic evaluation showed a lesion composed of alternating hypercellular areas made up of spindle-shaped cells and hypocellular areas with hyalinized, keloidal-like fibrous tissue. Occasional dilated vascular channels and entrapped pancreatic tissue were present within the lesion. Immunohistochemistry showed the lesion to be CD34, CD99, and bcl-2 positive. No evidence of atypia was noted, and the overall impression was of a benign solitary fibrous tumor of the pancreas. This is an unusual primary spindle cell neoplasm of the pancreas and should be considered in the differential diagnosis of all spindle cell lesions that occur in the pancreas.